Affective engineering in application to bi-level human migration models - Kalashnikov, Vyacheslav V.; Kalashnykova, Kalashnykova Ibanovna; Acosta Sánchez, Yazmín Guadalupe; Kalashnikov, Vitaly (Springer, 2014)
In this paper, we develop a bi-level human migration model using the concepts of affective engineering (Kansei Engineering) and conjectural variations equilibrium (CVE). In contrast to previous existing works, we develop a bi-level programming model in a natural form. The upper level agents are municipalities of competing locations, whose strategies are investments into the infrastructures of the locations (cities, towns, etc.). These investments aim at making the locations more attractive for both residents and potential migrants from other locations, which clearly demands affective engineering tools. At the lower level of the model, the present residents (grouped into professional communities) are also potential migrants to other locations. They make their decision where to migrate (if at all) by comparing the expected values of the utility functions of the outbound